Mesenchymal stem cells promote glioma neovascularization in vivo by fusing with cancer stem cells - Chao Sun; Xingliang Dai; Dongliang Zhao; Haiyang Wang; Xiaoci Rong; Qiang Huang; Qing Lan (BMC Cancer, 2019)
Abstract Background and objective Tumor angiogenesis is vital for tumor growth. Recent evidence indicated that bone marrow-derived mesenchymal stem cells (BMSCs) can migrate to tumor sites and exert critical effects on tumor growth through direct and/or indirect interactions with tumor cells. However, the effect of BMSCs on tumor neovascularization has not been fully elucidated. This study aimed to investigate whether fusion cells from glioma stem cells and BMSCs participated in angiogenesis. Methods SU3-RFP cells were injected into the right caudate nucleus of NC-C57Bl/6 J-GFP nude mice, and the RFP+/GFP+ cells were isolated and named fusion cells. The angiogenic effects of SU3-RFP, BMSCs and fusion cells were compared in vivo and in vitro. Results Fusion cells showed elevated levels of CD31, CD34 and VE-Cadherin (markers of VEC) as compared to SU3-RFP and BMSCs. The MVD-CD31 in RFP+/GFP+ cell xenograft tumor was significantly greater as compared to that in SU3-RFP xenograft tumor. In addition, the expression of CD133 and stem cell markers Nanog, Oct4 and Sox2 were increased in fusion cells as compared to the parental cells. Fusion cells exhibited enhanced angiogenic effect as compared to parental glioma cells in vivo and in vitro, which may be related to their stem cell properties. Conclusion Fusion cells exhibited enhanced angiogenic effect as compared to parental glioma cells in vivo and in vitro, which may be related to their stem cell properties. Hence, cell fusion may contribute to glioma angiogenesis.